Nationalism and Islam: Perspective of Egyptian and Syrian Muslim intellectuals - Ali, Muhamad (Indonesian Journal of Islam and Muslim Societies, 2014)
The problem of the relationship between nationalism and Islam has historicallyrevealed dynamic discourses, but seems to have gained little attention.This problem is important not only in understanding the modern discourseon Islam and nationalism but also in promoting a dialogue between Islamand the West. This paper attempts to show how the best known of Muslimintellectuals from Egypt and Syria during the 19th and first half of the 20thcentury, managed to fuse Islamic concepts and nationalism together into asingle, unified discourse. This paper approaches the question in two differentways. In order to provide a context, the first section reviews how nationalismemerged and influenced the Muslims. The next section studies how Muslimintellectuals have responded to foreign ideas in general and nationalism inparticular, and how some of them have attempted to work out a compromisebetween nationalism and Islam.Masalah hubungan antara nasionalisme dan Islam secara historismengungkapkan wacana dinamis, tetapi tampaknya telah mendapatkan sedikitperhatian. Masalah ini penting tidak hanya dalam memahami wacana modernIslam dan nasionalisme, tetapi juga dalam mempromosikan dialog antara Islam dan Barat. Tulisan ini mencoba untuk menunjukkan bagaimana intelektualMuslim ternama dari Mesir dan Suriah pada paruh ke-19 dan awal abad ke-20,berhasil memadukan konsep-konsep Islam dan nasionalisme bersama-samamenjadi satu wacana. Makalah ini mendekati persoalan ini dengan dua carayang berbeda. Dalam rangka memberikan konteks, bagian pertama mereviewbagaimana nasionalisme muncul dan mempengaruhi umat Islam. Bagianberikutnya mempelajari bagaimana intelektual Muslim telah merespon ideideasing pada umumnya dan nasionalisme pada khususnya, dan bagaimanabeberapa dari mereka telah berusaha untuk bekerja untuk mengkompromikanantara nasionalisme dan Islam.